RELATIONSHIP OF OBESITY WITH HYPERTENSION DISEASE IN PUSKESMAS LEGUNG, SUMENEP REGENCY - Safera Dewi Agustini; Nur Mujadiddah Mochtar; Muhammad Perdana Airlangga; Irma Kartikasari (PROCEEDING UMSURABAYA, 2023)
Hypertension is defined as an increase in systolic and diastolic blood pressure >140/90 mmHg in adults over the age of 18 years with at least 2 examinations. Obesity is overweight which is characterized by the results of a body mass index that is above normal. Measurement of body mass index can be done by measuring height, weight, upper arm circumference, as well as waist and hip circumference. The results of measurements of excess body mass index (obesity) are one of the factors that can trigger hypertension. Based on this, it is important to conduct research related to the relationship between obesity and hypertension. Objectives: To determine the relationship between obesity and hypertension at the Legung Health Center, Batang-Batang District, Sumenep Regency. Methods: Using an observational analytic method with a cross sectional approach. From 133 research populations, 100 samples were selected using the Slovin formula calculation. Simple random sampling technique was used for sampling to be used in a random sample of hypertensive patients. Research Results: The number of respondents who are obese is 75 people. A total of 87 respondents had grade II hypertension and 13 respondents had grade I hypertension. Statistical analysis using the Chi-Square method obtained p value = 0.626 (p>0.05) so it can be interpreted that there is no significant relationship between body mass index and hypertension. Conclusion: From the results of Chi-Square analysis, it is known that there is no significant relationship between body mass index and hypertension. Respondents with hypertension patients who are not obese may be due to the fact that patients always control their blood pressure by maintaining their diet by avoiding coconut milk and not eating fried foods.Keywords: hypertension, obesity, body mass index, chi-square